Pengaruh Metode Pembelajaran Karya Wisata terhadap Minat Belajar IPS pada Siswa Kelas 8 di SMPN 1 Ngunut - Nilna Barorotun Nada; Bagus Setiawan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to address the low interest in learning among students in the Social Studies subject at SMPN 1 Ngunut, caused by monotonous conventional teaching methods. The field trip method is implemented to provide direct learning experiences, linking theory to real practice. The research problem includes the influence of the field trip method on the interest in learning Social Studies among eighth-grade students. Using an associative quantitative approach, the research population consists of 386 students, with a sample of 40 students selected randomly. Data were collected through interviews, questionnaires, and documentation, and analyzed using simple linear regression. The results indicate a positive and significant influence of the field trip method on students' interest in learning Social Studies, with a strong effect of 64.2%. The t-value (7.935) exceeds the critical t-value (2.02439) with a significance level of 0.00, thus the alternative hypothesis is accepted. The correlation coefficient (R) of 0.790 indicates a strong relationship, meaning that the application of this method increases students' interest in studying Social Studies.